Clinical outcomes in pregnant women with coronavirus disease 2019 in a perinatal medical centre in Japan: a retrospective study of the first 1 year of the pandemic. (3rd October 2022) - Takahashi, Ken; Kobayashi, Yukari; Sato, Mariko; Nagae, Seika; Kondo, Ibuki; Funaki, Satoru; Sato, Taisuke; Konishi, Akiko; Ito, Yuki; Kamide, Taizan; Hoshina, Tokio; Kanuka, Hirotaka; et al.
Abstract: In this retrospective study, we analysed clinical and demographic data from the medical records of 31 pregnant women with coronavirus disease 2019 (COVID-19) who were treated at our hospital between April 2020 and April 2021. The most common symptom was a fever; ∼10% of patients were asymptomatic. One patient with rapidly worsening pneumonia needed a Caesarean Section at 30 weeks and was admitted for intensive care. Twelve patients received perinatal care in our hospital (10 live births, one stillbirth, and one artificial abortion). Six patients delivered vaginally; the others delivered via caesarean section. Two patients had complications, including severe hypertensive disorders and preeclampsia. All patients recovered from COVID-19. Severe acute respiratory syndrome coronavirus 2 was not detected in the placenta, umbilical cord, cord blood, amniotic fluid, vaginal fluid, or breast milk in any patient. There were no neonatal adverse outcomes. The possibility of transmitting the coronavirus to pregnancy-related samples was low. IMPACT STATEMENT: What is already known on the subject? COVID-19 has been affecting different countries in diverse ways, and the incidence, mortality, and morbidity rates of patients with COVID-19 vary widely by country or region and race. These differences in results may reflect racial differences and differences in national health care systems. Moreover, the information about the perinatal outcomes of pregnant women with COVID-19 and their newborns from Japan is limited. What do the results of this study add to what is known? We described the perinatal outcomes of 31 Japanese pregnant women with COVID-19 who were managed safely in a perinatal medical centre in Tokyo Japan, during the first 1 year of the pandemic. What are the implications of these findings for clinical practice and/or further research? Severe pneumonia and perinatal complications may occur, although no maternal and neonatal deaths were observed for COVID-19-positive pregnant women in our facility. Therefore, it is important to prevent this infection during pregnancy with the provision of effective medical care.